Non-interest income and bank profitability: Evidence from Tunisian banks (International Journal of Scientific Research and Management (IJSRM), 2021)
This study investigates the impact of banks’ diversified income structure on profitability among Tunisian banks during 2010-2018. We examine banks’ profitability using accounting and market measures as relevant indicators. We focus on each category of non-interest income separately rather than on non-interest income as an overall measure to provide a clearer analysis helping bank managers assess relevant strategies, and show that income structure diversification enhances banks’ profitability, albeit with their mixed effects. The empirical analysis of panel data indicates that Tunisian bank’s market-to-book value is very sensitive to all types of non-interest income. Banking activity diversification improves stock market profitability particularly in large banks and a safe macroeconomic environment. However, only fees and commissions incomes increase Tunisian banks’ assets profitability. Positive fees and commissions incomes’ effect is more pronounced for large banks and in a deflationary environment. We conclude by recommending to Tunisian banks, the diversification of their activities and the search for non-interest income while trying to control the costs of adopting these innovations, to take the necessary precautions, and to develop their personal skills.